Comorbidity and medication use in patients with angina due to a coronary vasomotion disorder. (3rd October 2022) - Blundell, H; Ambery, P; Arnold, M; Brookes-Smith, I; Kiddle, S; Greasley, P J; Berry, C
Abstract: Background: Microvascular angina and vasospastic angina are disorders of coronary vasomotion. The associations between these conditions, comorbidity and medication use in relatively unselected populations is not well described. Aim: To describe the proportions of patients with concomitant morbidity and related medication use in an international, contemporary, clinical database. Methods: TriNetX, a global federated health research network with access to anonymized electronical medical records (EMRs) from participating healthcare organizations including academic medical centres, specialty physician practices, and community hospitals, predominantly in the USA was used. The ICD10 code (I20.1) representing "Angina pectoris with documented spasm" was used as a primary search term. ICD10 codes were also used for cardiorenal and metabolic conditions. Medication use was classified as occurring prior to or on the date of the angina episode. The time-period for defining the analysis population was 01.01.2017–31.12.2019. The population age was ≥18 years. Results: Data were available on 12, 200 individuals (mean (SD) age 63 (13) years; 63% female). The % of individuals with a concomitant diagnosis is described in Table 1. Hypertension occurred in almost two thirds of individuals, an anxiety disorder affected more than one quarter and type 2 diabetes and/or obesity occurred in one fifth. Medication use is described in Table 2. Half of patients received a calcium channel blocker therapy. Nitroglycerin, beta-blockers, and isosorbide mononitrate were less commonly used (45%, 45% and 23%, respectively). Most (58%) patients were prescribed an antacid. Half of patients received statin treatment (50% overall; 36% atorvastatin) and insulin (12%) and metformin (9%) were the most commonly prescribed antidiabetic medications. Conclusions: Angina associated with coronary spasm associates with female sex and cardio-metabolic risk factors. Contemporary pharmacotherapy for diabetes and statins appear to be under-used. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): AstraZeneca